Mission life in Cree-Ojibwe country : memories of a mother and son - Brown, Jennifer S. H., 1940-; Young, Elizabeth Bingham; Young, E. Ryerson (Egerton Ryerson), 1869-1962 (Our lives--diary, memoir, and letters., 2014)
In May of 1868, Elizabeth Bingham Young and her new husband, Egerton Ryerson Young, began a long journey from Hamilton, Ontario, to the Methodist mission of Rossville. For the next eight years, Elizabeth supported her husband's work at two mission houses, Norway House and then Berens River. Her account of mission life is accompanied by that of her eldest son, ""Eddie."" Born at Norway House in 1869 and nursed by a Cree woman from infancy, Eddie was immersed in local Cree and Ojibwe life, culture, and language, in many ways exemplifying the process of reverse acculturation often in evidence amo.